Continuous Beta-Blocker Therapy Delays Structural Deterioration after Bioprosthetic Mitral Valve Replacement - Ma, Wenrui; Tan, Yan; Shi, Qiuxia; Xu, Zhiwei (The Thoracic and Cardiovascular Surgeon, 2019)
The impact of continuous beta-blocker (BB) therapy on structural valve deterioration (SVD) after bioprosthetic mitral replacement was investigated. From 2000 to 2005, 138 such patients were propensity score matched in a 1:1 fashion (continuous BB therapy after surgery, n = 69; without BB therapy, n = 69). Median follow-up was 12.3 years. Cardiac mortality was comparable between patients with and without BB therapy (p = 0.13), while the 10-year freedom from SVD was significantly higher in patients with BB therapy (92.4 vs. 76.3%, p = 0.001). In conclusion, continuous BB therapy may be considered in patients after bioprosthetic mitral valve replacement to delay SVD and improve prosthetic durability.
Keywords: mitral valve replacement; echocardiography; heart valve; surgery